Doing Knowledge Learning Model to Strengthen Media Production Skills: Feasibility Analysis and Implementation - Kristanto, Andi; Dewi, Utari (Journal of Education Technology, 2024)
Students face difficulties in graphic design practice. Currently, students rely on automatic templates on software such as Canva that facilitate the design process but do not support their understanding of the basics of graphics. This study aims to analyze the feasibility and effectiveness of developing a Doing Knowledge learning model to improve mastery of media production skills. The development research uses the ADDIE development model. The development stages include Analysis, Design, Development, Implementation, and Evaluation. This development produces a Doing Knowledge learning model for the Media Production course that meets the rules and provisions of learning media. Furthermore, validation is carried out by learning design experts and material experts to determine the feasibility of the learning model. Pretest and posttest data were analyzed using N-Gain to determine the increase in learning outcomes after implementing the learning model on the trial subjects. The trial subjects were the students in the Educational Technology study program who had taken the Media Production course. The findings showed that the results of the media expert test, material expert test, individual test, and small group test were very good criteria. In contrast, the effectiveness test using N-Gain showed a high category. This study concludes that Doing Knowledge is a feasible learning model to improve media production skills. This study recommends wider application of the model to other learning contexts based on practical and collaborative skills.